Pengaruh Penggunaan Media Digital terhadap Pembelajaran Bahasa Indonesia di Era Digital - Arum Dwi Anjani; Devy Lestari Nurul Aulia; Nada Tabriz; Dhini Triana Putri; Alya Susanti (Syntax Idea)
Learning is essentially an activity that guides students in undergoing teaching and learning activities so that they can achieve the desired learning goals of the educator. Teachers must be aware of the situation of students, starting from those who do not understand to those who understand. The learning process is also the main target for achieving educational goals. Efforts to change the curriculum continue to be carried out to improve the quality of learning and core skills. The main goal of curriculum development and change is to improve quality. The current Indonesian curriculum tends to be strict and too focused on content. Indonesian, as the official language spoken by more than 270 million people throughout Indonesia, plays a vital role in shaping the nation's identity and uniting people of diverse ethnicities, languages, and cultures. In a broader context, language serves as a means of communication and also as a mirror of the social and cultural dynamics of society. However, in the last two decades, rapid changes in information technology, especially through the emergence of social media, have led to a significant transformation among people, especially teenagers, in interacting with using Indonesian on social media.